KENDALA DALAM PEMBELAJARAN MICRO TEACHING DAN PEMECAHANNYA - Sulistyo, Edy Tri (Jurnal Inovasi Pendidikan, 2010)
This study aims to determine: (1) what constraints in microteaching lessons are faced by the students of Education Study Program at Teacher Training and Education Faculty, Sebelas Maret University Surakarta; and (2) what alternative solutions in overcoming the obstacles, so that students can join the microteaching lessons well. This research uses descriptive qualitative approach, with purposive sampling technique. Data sources include informants, place/event and archive/document.  The data are collected by in-depth interview techniques, direct observation, and content analysis. The content ?analysis is done by the technique of interactive models. Based on the result analysis, it can be concluded that the practice of microteaching is absolutely important to be given to the students as potential educators in the future. Due to the lack of facilities and infra-structures, and to maximize learning activities, it is important for the institution to give special space for the ideal microteaching room, to provide the adequate supporting facilities, and to improve the tutors' competence. Another constraint is that the students who take courses on learning component generally did not master the practical material such as how to draw on the blackboard. In addition, some students are less self-confident in the training. It can be solved by taking a great number of good training materials for teaching theory and practice.